2019
DOI: 10.1039/c9qi00905a
|View full text |Cite
|
Sign up to set email alerts
|

Double perovskite Cs2AgInCl6:Cr3+: broadband and near-infrared luminescent materials

Abstract: A Cr3+-doped halide double perovskite Cs2AgInCl6:Cr3+ is first reported which exhibits a broad near-infrared emission ranging from 850 to 1350 nm centered at 1010 nm with a FWHM of 180 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 259 publications
(200 citation statements)
references
References 49 publications
7
192
1
Order By: Relevance
“…We note that the newly-proposed SCAN-rVV10 functional is one of the strongly constrained and appropriately normed metageneralized gradient approximation (meta-GGA) functionals that is considered to model well metallic, insulating and semiconducting materials (Sun et al, 2015;Sun J. et al, 2016;Buda et al, 2017). The rVV10 part of the functional accounts for the non-local correlation part required to appropriately describe van der Waals (vdW) interaction (Peng et al, 2016;Chakraborty et al, 2018;Zhang et al, 2018;Anh et al, 2019). Bokdam et al have demonstrated that the SCAN functional accounts for short range dispersion effects-which conventional hybrid functionals do not account for-and is the most suitable functional to study the atomic structure of hybrid perovskite materials (Bokdam et al, 2017).…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the newly-proposed SCAN-rVV10 functional is one of the strongly constrained and appropriately normed metageneralized gradient approximation (meta-GGA) functionals that is considered to model well metallic, insulating and semiconducting materials (Sun et al, 2015;Sun J. et al, 2016;Buda et al, 2017). The rVV10 part of the functional accounts for the non-local correlation part required to appropriately describe van der Waals (vdW) interaction (Peng et al, 2016;Chakraborty et al, 2018;Zhang et al, 2018;Anh et al, 2019). Bokdam et al have demonstrated that the SCAN functional accounts for short range dispersion effects-which conventional hybrid functionals do not account for-and is the most suitable functional to study the atomic structure of hybrid perovskite materials (Bokdam et al, 2017).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Dynamically and Mechanically Stable Halide Double Perovskites are an important class of light harvesting materials for application in solar energy technology and optoelectronics (Greul et al, 2017;Matthews et al, 2017;Xiao et al, 2017;Zhao X.-G. et al, 2017;Chen et al, 2018;Lei et al, 2018;Luo et al, 2018;Tan et al, 2018;Xu et al, 2018;Chu et al, 2019;Zhao et al, 2019;Zhou Y. et al, 2019). They are characterized by the chemical formula A 2 BB ′ X 6 , where A is generally a monocationic organic or alkali metal species such as MA + (methyl ammonium), Cs + , Rb + ; B is an alkali metal ion or a transition metal atom in its +1 oxidation state (for example, Cu + , Ag + , Na + ); B ′ is a transition or main group metal ion in the +3 oxidation state (In 3+ , Bi 3+ , Sb 3+ , Cr 3+ ); and the X sites are occupied by halide ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For practical applications, luminescence quantum efficiency is a critical parameter. Calculation detail for Luminescence quantum efficiency is shown in supporting information, and MASN:0.07Mn 2+ is provided with 70.1% internal quantum efficiency (IQE) excited at 310 nm as shown in Figure , which is comparable to that of some Cr 3+ doping matrixes 14‐17 . The absorption efficiency (Abs) is relatively low, and is determined to be 36.6%.…”
Section: Resultsmentioning
confidence: 93%
“…Calculation detail for Luminescence quantum efficiency is shown in supporting information, and MASN:0.07Mn 2+ is provided with 70.1% internal quantum efficiency (IQE) excited at 310 nm as shown in Figure S4, which is comparable to that of some Cr 3+ doping matrixes. [14][15][16][17] The absorption efficiency (Abs) is relatively low, and is determined to be 36.6%. Upon 470 nm excitation, IQE and Abs are 47.1% and 19.8% respectively, much lower than those under 310 nm excitation.…”
Section: Luminescence Quantum Efficiencymentioning
confidence: 99%

Halide Double Perovskites

Pareja‐Rivera,
Zugasti‐Fernández,
Olalde‐Velasco
et al. 2023
Halide Perovskite Semiconductors